Interaksi Jarak Tanam dan Mulsa Jerami terhadap Produksi Tanaman Kedelai (Glycine max (L.) Merill) - Rahman Rahman; La Ode Afa; La Karimuna; La Ode Safuan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The low yield of soybeans is caused by drought, soft organic matter, and space for irregular plant growth. This study examines how plant spacing, and straw mulch dosage affect soybean yield. The research was conducted from August to December 2021 at the Field Laboratory of the Faculty of Agriculture, UHO. The research tools used in this study were tractors, hoes, ruler meters, ovens, analytical scales, and other supporting equipment. The materials consisted of soybean of the Anjasmoro variety, straw mulch, and other supporting materials. The study used a split-plot design arranged in a randomized block design. The main plot is the spacing (J) which consists of 2 levels, namely 20 cm x 20 cm (J1) and 20 cm x 30 cm (J2). Subplots were the dose of straw mulch (M) which consisted of three levels, namely without straw mulch (M0), 4 tons ha-1(M1), and 8 tons ha-1 (M2). The observed variables included the total number of pods per plant, weight of 100 seeds (g), seed weight per plant (g), harvest index (IP), and yield (tons). ANOVA analyzed data, and statistically different were tested by DMRT (α=0.05) using SAS 9.2. The interaction of plant spacing and straw mulch an increasing: the total number of pods, the weight of 100 grains, grain weight, harvest index, and yield. Plant spacing of 20 cm x 30 cm and the straw mulch of 8 t ha-1 (J2M2) obtained a product of 2.18 t ha-1 (an increase of 44.4%) compared to a spacing of 20 cm x 20 cm and without straw mulch (J1M0).